Corn Farming Development Strategies in Improving Food Security in Sabulakoa Village, Sabulakoa Sub-District, South Konawe District - Angel Puspita Sari; Ilma Saritamustaqiyma Rianse; Muhammad Aswar Limi (International Journal of Technology and Education Research, 2024)
Maize is one of the staple foods after rice/rice. In addition, corn is included in superior commodities so that it becomes the target of fulfilling food security. This study aims to identify farmers' development strategies in maintaining food security in Sabulakoa village, Sabulakoa sub-district, South Konawe district. The method used is descriptive method. The type of data used in this research is qualitative data. The population in this study were corn farmers totaling 20 people. Data analysis using SWOT Analysis with IFAS Matrix (Internal Factor Analysis Strategy) and EFAS Matrix (External Factors Analysis Strategy). The results showed that the strategy that can be used is the S-O strategy located in quadrant I by utilizing dry land area and experience in farming. So it is possible that the development of corn farming in Sabulakoa village has the strength to improve food security and take advantage of long-term opportunities. An aggressive development strategy can be started by maintaining good quality corn crops and providing abundant production so that it can meet demand and maintain food security in Sabulakoa Village